Robotic Competitions: Motivation for Engineering Programmes - V. Varalakshmi, V Kalyani, L. Hari Prasad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
e-Health is referred to in literature as the usage of information and communication technologies (ICT’s) in the health domain, to administer treatment of patients, research, health education and the monitoring of public health. South Africa is in the process of re-engineering its public healthcare to improve healthcare for all South African citizens. E- health forms part of the re-engineering process. The purpose of this paper is therefore to explore benefits and challenges of e-health as experienced in other countries. A list of both e-health benefits and e- health challenges are provided and could provide guidance in the implementation of e-health in South Africa. To realise the purpose of the paper, an inductive content analysis methodology was followed. The main results were that although the challenges outweighs the benefits in the provided lists, there is still hope that through proper ICT solutions the benefits of e-health can grow more rapidly. This can lead to improved e-health service delivery and citizens in countries can all benefit from this.